Alternatives in Jewish bioethics - Zohar, Noʻam (Albany : State University of New York Press, 1997)
A dialogue between contemporary, Western moral philosophy and the tradition of Legal/Moral Descourse (Halakha).
Front Matter -- Front Cover -- Half Title Page -- Title Page -- Copyright Page -- Table of Contents -- Acknowledgments -- Contents -- Introduction -- Authority in Nature -- Death: Natural Process and Human Intervention -- Parenthood: Natural Fact and Human Society -- God and Nature: A Summary -- Religious Humanism -- Elements of Religious Humanism -- Human Life. Human Lives: Assessing the Absolute -- Human Bodies: Long-Term Benefits and Symbolic Constraints -- Allocating Medical Resources: Global Planning and Immediate Obligations -- Back Matter -- References -- Index -- Back Cover.
Includes bibliographical references (pages 153-160) and index.
Print version record.
English.
JSTOR
Keywords: Medicine -- Religious aspects -- Judaism; Bioethics; Medical laws and legislation (Jewish law); Jewish ethics; Humanities; Sociology; Art; Suicide; Culture; Hospice care; Terminal care; Health services accessibility; Health planning; Medical personnel; Reproductive technology; Social psychology; Economics; Death; Methodology; Medical care; Social sciences; Social problems; Ethnology; Therapeutics; Anthropology; National health services; Public health; Diseases; Human behavior; Theology; Euthanasia; Cultural pluralism; Do-not-resuscitate orders; Assisted suicide; Humanism; Religion; Human reproductive technology; Philosophy; Judaism; Dead; Social values; Humanities; Sociology; Art; Suicide; Culture; Terminal Care; Health Services Accessibility; Health Planning; Health Occupations; Epidemiologic Research Design; Reproductive Techniques; Psychology, Social; Health Care Quality, Access, and Evaluation; Withholding Treatment; Economics; Homicide; Death; Research Design; Methods